Evaluation of the Operations of Liquefied Petroleum Gas Refilling Plants in Ghana – A Case Study - Broni-Bediako, E.; Amorin, R. (Journal of Energy and Natural Resource Management, 2016)
The demand for Liquefied Petroleum Gas (LPG) in Ghana has increased over the years since the Government LPG Promotion Programme in 1990 and has resulted in the rise of the operations of LPG refilling plants in Ghana especially in the urban areas. The operations of these refilling plants have raised a lot of concerns among the general public over the years due to its associated accidents. The study aimed at evaluating the operations of LPG refilling plants in Ghana using Tarkwa as the study area. It adopted survey as its research design and supported with literature review. The main instrument used for data collection was a questionnaire. Data collected from five refilling plants were analysed using statistical methods as well as the grading criteria prescribed by National Petroleum Authority (NPA) of Ghana. None of the LPG refilling plants attained “Grade A”. It is recommended that there should be constant monitoring on the operations of LPG refilling plants to ensure total compliance with standards.